2016
DOI: 10.4196/kjpp.2016.20.6.605
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of serotonin-induced contraction of rat mesenteric artery by ketamine

Abstract: Ketamine is an anesthetic with hypertensive effects, which make it useful for patients at risk of shock. However, previous ex vivo studies reported vasodilatory actions of ketamine in isolated arteries. In this study, we reexamined the effects of ketamine on arterial tones in the presence and absence of physiological concentrations of 5-hydroxytryptamine (5-HT) and norepinephrine (NE) by measuring the isometric tension of endothelium-denuded rat mesenteric arterial rings. Ketamine little affected the resting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
(57 reference statements)
2
10
0
Order By: Relevance
“…The direct effects of ketamine and PCP on dopamine D 2 and serotonin 5-hydroxytryptamine (HT) 2 receptors have been suggested to be implicated in the pathogenesis of schizophrenia 8 11 . In agreement with this, a previous study showed that 5-HT 2A receptor (5-HT 2A R)-mediated arterial contraction was facilitated by ketamine 12 , which was suggested to be the mechanism underlying ketamine-induced hypertension. In addition, NMDAr antagonists, including MK801 and ketamine, enhanced the head-twitch response, a 5-HT2R-mediated behavior, in reserpine-treated mice 13 .…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…The direct effects of ketamine and PCP on dopamine D 2 and serotonin 5-hydroxytryptamine (HT) 2 receptors have been suggested to be implicated in the pathogenesis of schizophrenia 8 11 . In agreement with this, a previous study showed that 5-HT 2A receptor (5-HT 2A R)-mediated arterial contraction was facilitated by ketamine 12 , which was suggested to be the mechanism underlying ketamine-induced hypertension. In addition, NMDAr antagonists, including MK801 and ketamine, enhanced the head-twitch response, a 5-HT2R-mediated behavior, in reserpine-treated mice 13 .…”
Section: Introductionsupporting
confidence: 76%
“…1d ). Similarly, the facilitating effect of ketamine 12 was not observed when the E m -dependent 5-HT response was excluded (Fig. 1e ).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations